Comparison of heavy metals (Cd, Zn and Cu) concentrations in sediments between closed and open aquaculture system - Hamizi Hafezah.
Linggi estuary and Bangi have the potential to become an establish sites for aquaculture. Due to safety factor, the sediments at the sites had been taken to be analyzed. The concentration level in heavy metal for Cu, Cd and Zn were analyzed by using the atomic absorption spectrophotometer. The concentration of Zn and Cu were high while Cd is less concentrated. Between these two sites,the open aquaculture system (Linggi estuary) has the higher concentration of heavy metals compare to the closed aquaculture system (Bangi). The source of trace metals in these two sites mostly are from the antropogenic activites such as tourism, uses of pesticides and many more. This study is important because almost every day people eat fish and did not know the level of heavy metals that accumulate in the fish. The fish can accumulate the heavy metals through the sediment. Indirectly, it will cause diseases as we are the third consumer will eat that fish and accumulate heavy metal bit by bit. The bad effect will shows after a long period of time. This will not only affect us but it also effects the surrounding environment. This study should be conducted from time to time to check the heavy metal concentrations.